Sobre la Intencionalidad Afectiva de Scheler - Hackett, J. Edward (Revista del Centro de Investigación de la Universidad la Salle, 2018)
The following essay was first given as a virtual lecture on April 12, 2018 to La Salle University. The scope of the lecture was expository and had two aims. First, I explained how Scheler’s affective intentionality undergirds moral theorizing. Second, I explained Scheler’s value rankings disclosed in affective intentionality. Overall, I hoped to convey to the audience how unique Scheler’s position in the history of ethics is.